The impact of tax structures on deficits: tax elasticity and fiscal illusion in sixteen OECD countries - Royed, Terry J.; Borrelli, Stephen A. (1999)
This paper represents the first systematic attempt to link revenue structure to deficits cross-nationally. Recent analyses of the causes of increased budget deficits in the industrialized countries have focused on the factors that influence government spending, ignoring the possibility that chronic deficits might also be caused by shortfalls in revenue. In this research, using data from sixteen OECD countries during the period 1959-1990, we test hypotheses regarding the linkage between a country's revenue structure and its experience with deficits. We find evidence that countries heavily dependent on direct taxes had more difficulty keeping spending and revenues in line, particularly during times of high unemployment. We find no evidence, however, of a "fiscal illusion" impact on deficits. - Reproduced
Keywords: Revenue; Public finance